Failure of doramectin and ivermectin in preventing Cochliomyia hominivorax myiasis in a subtropical region: A pharmacokinetic-pharmacodynamic study - Muchiut, Sebastian; Miró, Maria Victoria; Anziani, Oscar Sergio; Nava, Santiago; Lifschitz, Adrian Luis (Elsevier, 2025)
The aim of this work is to present a case study where the failure of IVM 3.15 % and DRM 1 % to prevent natural infestations of C. hominivorax larvae in Argentina is investigated based on field efficacy tests and a pharmacokinetic and pharmacodynamic analysis. Thirty male crossbred Braford calves were randomly assigned to three experimental groups (n = 10), the IVM 3.15 % group (subcutaneously at 630 µg/kg), the DRM 1 % group (subcutaneously at 200 µg/kg) and the control group (saline solution subcutaneously). All treatments were performed at the time of castration surgery through a scrotal incision, and the wounds were exposed to natural infestations of C. hominivorax. Wound inspections were carried out on days 3, 6, and 13 post-treatments. Jugular blood samples were taken from experimental animals at 3- and 6-days post-treatment. In presence of C. hominivorax larvae, samples of both the larvae and wound secretions were collected in plastic vials on days 3 and 6 to measure concentrations of both drugs by high-performance liquid chromatography. On day 3 post-treatment, active myiasis was observed in 9 animals from the control group, 5 from the IVM 3.15 % group, and 6 from the DRM 1 % group. On day 6 post-treatment, 5 and 3 new myiasis were detected in the IVM 3.15 % and DRM 1 % group, respectively. No larvae were observed in the wounds on day 13 post-treatment. Interestingly, DRM concentrations tended to be higher in larvae compared to IVM on day 3 post-treatment (p = 0.051), and IVM plasma concentrations tended to be higher than those measured for DRM on day 6 (p = 0.087). There was a very strong correlation between DRM and IVM concentrations in plasma and wound secretions and larvae. The uptake of DRM from wound secretions to larvae was 83 % greater than that of IVM (p = 0.03). The results of this trial suggest the presence of C. hominivorax resistance to DRM and highlight concern about the lack of effectiveness of IVM 3.15 % in preventing C. hominivorax infestations.